Opinions of hemodialysis and peritoneum patients regarding depression and psychological problems which they experience: A qualitative study - Elif Unsal Avdal; İsmail Ayvaz; Berna Nilgun Özgursoy Uran; Julide Gülizar Yildirim; Funda Sofulu; Gülseren Pamuk (Elsevier, 2020)
Background: Dialysis are the treatment modalities that affect the quality of life. The objective of this qualitative study is to reveal how hemodialysis and peritoneal dialysis patients perceive depression and psychological problems which they experience. Methods: An interpretative phenomenological analysis approach, as espoused by Smith and Osborn provided the framework for this study. The study was performed in hemodialysis and peritoneal dialysis units of a university hospital. 10 adult hemodialysis patients and 10 adult peritoneal dialysis patients, selected. In-depth, semi-structured, face-to-face interviews were held with the patients. All interviews were digitally recorded and subjected to qualitative analysis after transcription. Results: Analysis revealed themes suggesting that hemodialysis and peritoneal dialysis patients frequently experienced depression as well as psychological problems such as decreased social support, burnout, despair, and anxiety. Conclusions: It was concluded as a result of this study that the prolonged hemodialysis and peritoneal dialysis process negatively affected patients with chronic kidney disorders.